Penerapan Arsitektur Tropis pada Sentra Pelatihan dan Edukasi Ibu dan Anak Nelayan di Desa Otiola Ponelo Kepulauan - Deys Linda Fatubun; Kalih Trumansyahjaya; Nur Mutmainnah (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Abundant natural resource potential is found in one of the villages in Gorontalo such as fish, shrimp, clams, squid, crabs, seaweed, mangroves, and coconuts in Otiola Village, Ponelo Islands Sub-district, however, limited knowledge and skills in processing catches and managing natural resources hinder the improvement of the community's economy. The majority of fishermen's catches are sold directly without being processed into value-added products. Government assistance, such as sewing machines, coconut grating machines and seaweed seeds, are often not optimally utilized, indicating the need for training facilities to improve skills and innovation. The problems faced by the people of Otiola Village, especially mothers, are economic constraints, although some of them already have small businesses, such as selling food, cakes and drinks. In addition, the constraints faced by children in this village are lack of knowledge of social media utilization, limited access to education and skills, lack of proper playgrounds, lack of support for economic education so they need skills education and proper play facilities to support their development. Training in seafood processing, entrepreneurship, and digital promotion are urgent needs for the Otiola Village community to empower local potential. The center is designed to address these needs with a tropical architectural approach with a building design that maximizes air circulation, natural lighting, and the use of environmentally friendly materials. Therefore, to support the improvement of the quality of life of mothers and children in Otiola Village, both in terms of education and welfare, by providing various facilities such as classrooms, libraries, display areas, product marketing places, seafood reception areas, and children's learning and playing spaces. With these facilities, it is expected that the community's economy will improve through the products produced with economic value and the improvement of the skills of mothers and children of  Otiola Village.